HAKIKAT PENGALAMAN KEAGAMAAN DAN EKSPRESI KEBERAGAMAAN DALAM PANDANGAN JOACHIM WACH - sari, tia; randa, syafrinal (JURNAL AL-AQIDAH, 2023)
The writing of this article aims to examine Joachim Wach's ideas about the nature of religious experience and religious expression. In this study, using a qualitative approach with descriptive, exporative and analytical methods aimed at understanding what Joachim Wach meant by the nature of religious experience and expression of religion. This article also interprets or contextualizes Wach's ideas on religious phenomena in Indonesia. Nature of religious experience according to Joachim Wach is actually an individual or group experience that is inner between man and God. This relationship is always identified with one that cannot be studied or traced. Joachim Wach claims that the inner relationship between man and God will, of course, be traceable, giving rise to various religious expressions. Religious experience will tend to be expressed in three kinds of religious expressions, in the form of thoughts, actions and expressions of organizations or conspiracies.